A Survey on Enhanced MapReduce Spatial Hadoop in Cloud Computing - Vetrivelan, N; Jasmin Selvi, C (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is creating as a new computational worldview shift. Hadoop-MapReduce has become a powerful Calculation Model alternately handling huge information on Dispersed thing equipment groups such as Clouds. In all Hadoop implementations, the shortcoming FIFO scheduler is accessible where employments are booked in FIFO request with support alternately other Need based schedulers also. In this paper we study distinctive scheduler changes conceivable with Hadoop and too given some guidelines on how to improve the Planning in Hadoop in Cloud Environments.